The “cruel abandonment” in medicine. The struggle against doctors’ inaction in cases of sudden death in the 18th century - Fusco, Roberta; Iorio, Silvia; Ciliberti, Rosagemma; Picozzi, Mario (Acta Biomedica Atenei Parmensis, 2025)
In 1755, the medical field in Milan was characterized by a worrying reluctance of surgeons to intervene in cases of sudden death. This hesitancy, based on an alleged certainty of death founded on unreliable signs, caused considerable concern among local authorities and medical professionals. In an unpublished document, Doctor Guglielmo Parini, eminent member of the Illustrious Tribunal of Holiness of Milan, an institution responsible for supervising the health of citizens, expressed his dismay at the “cruel abandonment” of individuals considered dead without a thorough examination. His observations were based on numerous cases of presumed corpses, in which many individuals believed dead were actually alive, with their lives sacrificed due to misdiagnosis. Parini cites some of these cases of apparent death, taken from the dissertation of the famous anatomist Winslow, published eleven years earlier, in which the uncertainty of the signs of death was discussed. Through the analysis of a text dated to 1775, we try to bring to light an aspect that characterized 18th century forensic medicine.